Apoptosis of Colorectal Cancer Cell on Sprague-Dawley Rats Induced with 1,2 Dimethylhidrazine and Phyllanthus niruri Linn Extrac - Endang Sawitri (Chemical Engineering Diponegoro University, 2016)
Apoptosis cell is one of the main biomolecular predictors to determine kind of treatment given to patient with colorectal cancer and to predict the end result. Phyllanthus niruri Linn (P. niruri L) acts as antineoplastic but its potency on the process of cancer cell apoptosis has not been revealed yet. The objective of the research was to evaluate the apoptosis index of rats with colorectal cancer treated with and without P. niruri L. extract. This research used The Randomized Posttest-Only Control Group Design. As many as 30 male Sprague-Dawley rats were induced with 1,2 DMH 30 mg/kgBW once in every week. Four rats were sacrificed at week 9th, 11th and 13th to be observed the development of colorectal cancer. Induction was then stopped and other 18 rats were randomly located into two groups. The first group was positive control (K+) group consisted of 9 rats without P. niruri extract. The second group (X) was consisted of 9 rats with the application of P.niruri L. extract 13.5 mg/kg per day orally. All rats were terminated on week 19th, tumor lesion was proceed for Histopathology preparations and stained with Kit TUNEL-IHC (Apo-BrdU-IHCTM BioVision Cat #K403) to identify the apoptosis cell. Data were analyzed using unpaired t-test with significant level of p<0.05. The result showed that the average of apoptosis index of X treatment was 2.37 + 0.48 higher than K+ treatment namely 1.45 + 0.41 with a highly significance difference (p=0.000). Phyllanthus niruri L extract increased the apoptosis of colorectal cancer of Sprague-Dawley rats induced with 1,2 Dimethylhidrazine